Improving Students’ Speaking Skill through Students Vlog Project as PBL Output on Online Speaking Class - Zubaidi, Zubaidi; Suharto, Ririn Pratiwi; Rahayu, Eka Listianing (Universitas Nahdlatul Ulama Blitar, 2021)
The aim of this research is to investigate the implementation and the result of project-based learning by using vlog as the output of learning process to increase students’ speaking skill. This research used mixed methods design (qualitative and quantitative research). The result of this research was the implementation of PBL successfully improved students’ speaking skill in five crucial aspects of speaking, pronunciation, grammar, fluency, vocabularies and comprehension in average of 27% based on the post-test given to them. Then, there were 89% of the students from observation and questionnaire results agreed that this PBL implementation was helping them in the speaking online learning during Covid-19 pandemic.